Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1677/joe-09-0420
|View full text |Cite
|
Sign up to set email alerts
|

Acute cytokine-mediated downregulation of the zinc transporter ZnT8 alters pancreatic β-cell function

Abstract: Genetic studies suggest that Zn transporters such as ZnT8 play a role in insulin secretion by pancreatic β-cells; however, little is known about the dynamic roles of Zn trafficking pathways on β-cell physiology. To test the acute effects of the inflammatory cytokines interleukin 1β (IL1β) and tumor necrosis factor α (TNFα) on Zn homeostasis, the mRNA expression profile of Zn transporters of the ZnT and ZIP families was examined. Exposure of MIN6 cells or primary murine islets to IL1β or TNFα altered the mRNA e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 73 publications
8
37
1
Order By: Relevance
“…The results of the present study, in agreement with the findings of previous studies (27,46), indicated that insulin secretion can be inhibited by proinflammatory cytokines causing dysregulation of β cells via ZnT8 downregulation, and a decrease in β cell number by affecting apoptosis. The current study showed that proinflammatory cytokines, TNF-α and IL-1β, downregulate ZnT8 protein expression in NIT-1 cells.…”
Section: A B Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of the present study, in agreement with the findings of previous studies (27,46), indicated that insulin secretion can be inhibited by proinflammatory cytokines causing dysregulation of β cells via ZnT8 downregulation, and a decrease in β cell number by affecting apoptosis. The current study showed that proinflammatory cytokines, TNF-α and IL-1β, downregulate ZnT8 protein expression in NIT-1 cells.…”
Section: A B Discussionsupporting
confidence: 93%
“…The current study showed that proinflammatory cytokines, TNF-α and IL-1β, downregulate ZnT8 protein expression in NIT-1 cells. This effect was previously observed in MIN6 cells (27), indicating that decreased ZnT8 expression may contribute to impaired β cell function and insulin secretion. ZnT8 is predominantly expressed in pancreatic islets, and is responsible for transporting zinc from the cytoplasm into insulin secretory vesicles, where insulin is stored as a solid hexamer bound with two Zn 2+ ions (15).…”
Section: A B Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…While 5 ng/ml IL-1β suppresses both the proliferation of β-cells and their secretion of insulin [21], lower IL-1β concentrations (e.g. 0.02 ng/ml) promote β-cell proliferation and insulin secretion [22].…”
Section: Il-1β Production Is Induced In T2d Isletsmentioning
confidence: 99%
“…Twenty micrograms of protein were separated by 10% SDS-PAGE and transferred to a polyvinylidene fluoride membrane in a semidry apparatus. Western blot analyses were performed as previously described (El Muayed et al 2010). For SP-D samples, both reduced and nonreduced protein samples were examined.…”
Section: Western Blotmentioning
confidence: 99%